2018
DOI: 10.1051/0004-6361/201630358
|View full text |Cite
|
Sign up to set email alerts
|

Well-defined EUV wave associated with a CME-driven shock

Abstract: Aims. We report on a well-defined EUV wave observed by the Extreme Ultraviolet Imager (EUVI) on board the Solar Terrestrial Relations Observatory (STEREO) and the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO). The event was accompanied by a shock wave driven by a halo CME observed by the Large Angle and Spectrometric Coronagraph (LASCO-C2/C3) on board the Solar and Heliospheric Observatory (SOHO), as evidenced by the occurrence of type II bursts in the metric and dekameter-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Further, we found that the EUV wave propagates ahead of the CME leading edge using the STEREO-A and LASCO data sets. This supports the earlier findings and models that the EUV wave is driven by CME (Ma et al, 2011;Vourlidas, 2009, 2012;Cunha-Silva, Fernandes, and Selhorst, 2015;Cunha-Silva et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Further, we found that the EUV wave propagates ahead of the CME leading edge using the STEREO-A and LASCO data sets. This supports the earlier findings and models that the EUV wave is driven by CME (Ma et al, 2011;Vourlidas, 2009, 2012;Cunha-Silva, Fernandes, and Selhorst, 2015;Cunha-Silva et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Because chromospheric Moreton waves were believed to be driven by the flare pressure pulses for a long time since Uchida (1968), solar physicists naturally thought at the beginning that EUV waves also have the same driving mechanism (e.g., Khan & Aurass 2002;Hudson et al 2003;Warmuth et al 2004). However, more and more recent high-resolution observational studies have shown that EUV waves are in fact bow shocks driven by CMEs instead of flare pressure pulses (e.g., Patsourakos & Vourlidas 2009;Kienreich et al 2009;Patsourakos et al 2010;Chen 2006;Shen & Liu 2012a,c;Shen et al 2017a;Xue et al 2013;Long et al 2017b;Cunha-Silva et al 2018;Liu et al 2011b). Further investigations indicated that EUV waves can also be excited by other kinds of slightly different processes, such as newly-formed expanding loops, coronal jets, and mini-filament eruptions in small scales (e.g., Podladchikova et al 2010;Zheng et al 2012Zheng et al , 2013Su et al 2015;Shen et al 2017a), and the sudden expansion of transequatorial loops driven by coronal jets in large scales (Shen et al 2018e,d) .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the Atmospheric Imaging Assembly (AIA) on board Solar Dynamics Observatory (SDO) allowed to acquire observation data with unprecedented high spatial and temporal resolutions, revealing more detailed features of EUV waves. Events with both wave and non-wave components are found to be very common (Chen & Wu 2011;Asai et al 2012;Liu et al 2013;Cunha-Silva et al 2018;Fulara et al 2019). Such observations are also supported by three-dimensional (3D) models (Cohen et al 2009;Downs et al 2012).…”
Section: Introductionmentioning
confidence: 61%